Lateral Collateral Ligament Injury About the Knee: Anatomy, Evaluation, and Management. Issue 6 (15th March 2018) - Grawe, Brian; Schroeder, Amanda J.; Kakazu, Rafael; Messer, Malynda S.
Abstract : The lateral collateral ligament is the primary varus stabilizer of the tibiofemoral joint. Diagnosing an injury to this ligament can be challenging in the setting of multiligamentous trauma; however, failure to recognize these injuries can result in instability of the knee and unsatisfactory outcomes after cruciate ligament reconstruction. Recent literature exploring the anatomy and biomechanics of the lateral collateral ligament has enhanced our understanding and improved diagnosis and management of these injuries. Physical examination and imaging studies also are important in diagnosis and can facilitate classification of lateral collateral ligament tears, which affects treatment decisions. Nonsurgical, reparative, and reconstructive techniques can all be used to manage lateral collateral ligament injury about the knee; the optimal treatment is selected on the basis of injury severity.